Factors Related to Early Menarche in Adolescent Girls at Muhammadiyah 4 Junior High School East Jakarta - Nastiti Dyah Prastiwi; Rr. Arum Ariasih; Nurfadhilah; Nur Romdhona (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The age of menarche varies from the age range of 10-16 years and is said to be normal if it occurs at the age of 12-14 years. Nationally, the average menarche aged 13-14 years occurs in 37.5% of girls in Indonesia, with the prevalence of early menarche reaching 20.9%. Statistical results in Indonesia show that the age of menarche has decreased from an average age of 14 years to 12-13 years. Objective: This research aims to see what factors are associated with adolescent girls’ early menarche. Method: This type of research is quantitative with a cross-sectional study design. The research design in this study is analytical observational. The sample in this study was 56 respondents. Result: There is no statistically significant relationship but there is a substantial relationship between the frequency of consumption of junk food with age of menarche (p-value=1.000 and OR=1.104), physical activity with age of menarche (p-value=0.759 and OR=1.609), sleep rest with adolescent girls’ early menarche (p-value=0.958 and OR=1.224), and mothers’ menarche age with adolescent girls’ early menarche (p-value=0.867 and OR=1.389). Conclusion: There is no statistically significant relationship but there is a substantial relationship between the frequency of consumption of junk food, physical activity, sleep rest, and mothers’ menarche age with adolescent girls’ early menarche. Adolescent girls are expected to maintain good consumption patterns and avoid excessive consumption of junk food, carry out regular and not too-heavy physical activity, and have adequate sleep rest time at night so that they can avoid early menarche and the risk of various diseases in the future.